2014
DOI: 10.1136/amiajnl-2014-002817
|View full text |Cite
|
Sign up to set email alerts
|

Reducing caregiver stress with internet-based interventions: a systematic review of open-label and randomized controlled trials

Abstract: Internet-based interventions were mostly effective in reducing aspects of caregiver stress and improving their well-being. Further studies to assess outcomes for caregivers and their recipients' health, different technology delivery methods, and the cost of such interventions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 67 publications
(104 reference statements)
3
60
0
Order By: Relevance
“…• In about 2/3 of studies, caregivers who use Internet-based services have significantly reduced stress and improved quality of life for MH disorders [12]. They use interactive communities to bulletin board therapy groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…• In about 2/3 of studies, caregivers who use Internet-based services have significantly reduced stress and improved quality of life for MH disorders [12]. They use interactive communities to bulletin board therapy groups.…”
Section: Methodsmentioning
confidence: 99%
“…Many Internet-based materials and opportunities to learn exist for caregivers of patients, for those with MH (dementia, schizophrenia, anorexia) and medical disorders [12]. Services included webcasts, discussion boards, online classes, learning modules, and chat rooms; the best outcomes were best for satisfaction and comfort with services via cell phones [61].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, different reviews pointed out that programs addressing family caregivers of older people should take advantage of interactivity, connecting caregivers to peers and professional staff [11,24]. The online group component seem actually to be the most used and valued one of any given website, application or intervention [13].…”
Section: Peer Support Programsmentioning
confidence: 99%
“…Research evidence demonstrated that support services delivered via the web can effectively support family caregivers of older people in needs of help, sustaining their psychological and social wellbeing, enhancing confidence and self-efficacy [8][9][10][11][12]. Among the advantages, these services allow caregivers also to overcome time and logistic barriers to access support services [13].…”
Section: Introductionmentioning
confidence: 99%